"Founder crops" v. wild plants: Assessing the plant-based diet of the last hunter-gatherers in southwest Asia. (15th April 2018) - Arranz-Otaegui, Amaia; González Carretero, Lara; Roe, Joe; Richter, Tobias
Abstract: The Natufian culture (c. 14.6–11.5 ka cal. BP) represents the last hunter-gatherer society that inhabited southwest Asia before the development of plant food production. It has long been suggested that Natufians based their economy on the exploitation of the wild ancestors of the Neolithic "founder crops", and that these hunter-gatherers were therefore on the "threshold to agriculture". In this work we review the available data on Natufian plant exploitation and we report new archaeobotanical evidence from Shubayqa 1, a Natufian site located in northeastern Jordan (14.6–11.5 ka cal. BP). Shubayqa 1 has produced an exceptionally large plant assemblage, including direct evidence for the continuous exploitation of club-rush tubers (often regarded as "missing foods") and other wild plants, which were probably used as food, fuel and building materials. Taking together this data we evaluate the composition of archaeobotanical assemblages (plant macroremains) from the Natufian to the Early Pre-Pottery Neolithic B (EPPNB). Natufian assemblages comprise large proportions of non-founder plant species (>90% on average), amongst which sedges, small-seeded grasses and legumes, and fruits and nuts predominate. During the Pre-Pottery Neolithic, in particular the EPPNB, the presence of "founder crops" increases dramatically and constitute up to c. 42% of the archaeobotanical assemblages on average. Our results suggest that plant exploitation strategies during the Natufian were very different from those attested during subsequent Neolithic periods. We argue that historically driven interpretations of the archaeological record have over-emphasized the role of the wild ancestors of domesticated crops previous to the emergence of agriculture. Highlights: Review of the available evidence for plant exploitation during the Natufian. >65000 plant macroremains from two in situ early Natufian fireplaces. New evidence for the exploitation of club-rush tubers 14400 years ago. Predominant exploitation of non-founder wild plants during the Natufian.